2014
DOI: 10.3109/03630269.2014.979997
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Status and Plasma Lipid Profile in β-Thalassemia Patients

Abstract: β-Thalassemia (β-thal) is a genetic disorder, representing a major health problem in Algeria. It is associated with altered lipid levels and a state of oxidative stress that can lead to cardiac complications and premature death. We examined the plasma lipid profile and redox status of 46 patients with β-thal major (β-TM) and β-thal intermedia (β-TI) compared to 36 healthy subjects. Plasma lipids including total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C) and low-density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…Several studies have already described the generation of ROS in erythrocytes and their significance in the physiopathology of beta-thalassemia. Some of them have shown that this increase is higher in BTM than BTI, both in plasma and erythrocytes [46, 47]. Besides corroborating these findings, our results also described increased levels of ROS in mononuclear cells and neutrophils of these patients, indicating that oxidative damages are not restricted to erythroid cells (Fig 1).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have already described the generation of ROS in erythrocytes and their significance in the physiopathology of beta-thalassemia. Some of them have shown that this increase is higher in BTM than BTI, both in plasma and erythrocytes [46, 47]. Besides corroborating these findings, our results also described increased levels of ROS in mononuclear cells and neutrophils of these patients, indicating that oxidative damages are not restricted to erythroid cells (Fig 1).…”
Section: Discussionsupporting
confidence: 90%
“…The abnormality of plasma lipid profile in thalassemic patients including decreased levels of total cholesterol, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), together with increased levels of triglycerides have been reported [26][27][28]. Our results showed the altered levels of apolipoprotein A-I, A-IV, C-II, and E in response to the treatments.…”
Section: Discussionsupporting
confidence: 60%
“…They concluded that β -thalassemia minor RBCs react to increased OxS rising activities of antioxidant enzymes, while in β -thalassemia major normal antioxidant enzyme levels are due to the presence of normal RBCs from multiple blood transfusions. However, Boudrahem-Addour et al [ 27 ] observed a significant increase ( p < 0,05) of catalase activity in β -thalassemia major and intermedia. The present results, in concordance with Gerli et al [ 26 ], showed that some BTT subjects had increased catalase activity.…”
Section: Discussionmentioning
confidence: 98%